Factors influencing the efficacy of recombinant tissue plasminogen activator: Implications for ischemic stroke treatment - Víteček, Jan; Vítečková Wünschová, Andrea; Thalerová, Sandra; Gulati, Sumeet; Kubala, Lukáš; Capandová, Michaela; Hampl, Aleš; Robert Mikulík (PloS one, 2024)
Intravenous thrombolysis with a recombinant tissue plasminogen activator (rt-PA) is the first-line treatment of acute ischemic stroke. However, successful recanalization is relatively low and the underlying processes are not completely understood. The goal was to provide insights into clinically important factors potentially limiting rt-PA efficacy such as clot size, rt-PA concentration, clot age and also rt-PA in combination with heparin anticoagulant. We established a static in vitro thrombolytic model based on red blood cell (RBC) dominant clots prepared using spontaneous clotting from the blood of healthy donors. Thrombolysis was determined by clot mass loss and by RBC release. The rt-PA became increasingly less efficient for clots larger than 50 μl at a clinically relevant concentration of 1.3 mg/l. A tenfold decrease or increase in concentration induced only a 2-fold decrease or increase in clot degradation. Clot age did not affect rt-PA-induced thrombolysis but 2-hours-old clots were degraded more readily due to higher activity of spontaneous thrombolysis, as compared to 5-hours-old clots. Finally, heparin (50 and 100 IU/ml) did not influence the rt-PA-induced thrombolysis. Our study provided in vitro evidence for a clot size threshold: clots larger than 50 μl are hard to degrade by rt-PA. Increasing rt-PA concentration provided limited thrombolytic efficacy improvement, whereas heparin addition had no effect. However, the higher susceptibility of younger clots to thrombolysis may prompt a shortened time from the onset of stroke to rt-PA treatment.
Keywords: Tissue Plasminogen Activator; Thrombolytic Therapy; heparin; erytrocyty; cévní mozková příhoda; Heparin; Blood Coagulation; trombolytická terapie; lidé; rekombinantní proteiny; Recombinant Proteins; Stroke; fibrinolytika; ischemická cévní mozková příhoda; Erythrocytes; Ischemic Stroke; tkáňový aktivátor plazminogenu; Fibrinolytic Agents; hemokoagulace; Humans